A qualitative synthesis of gastro-oesophageal reflux in bronchiectasis: Current understanding and future risk. (August 2018) - McDonnell, M.J.; O'Toole, D.; Ward, C.; Pearson, J.P.; Lordan, J.L.; De Soyza, A.; Loebinger, M.; Chalmers, J.D.; Laffey, J.G.; Rutherford, R.M.
Abstract: Gastro-oesophageal reflux disease (GORD) is a common comorbidity in bronchiectasis, and is often associated with poorer outcomes. The cause and effect relationship between GORD and bronchiectasis has not yet been fully elucidated and a greater understanding of the pathophysiology of the interaction and potential therapies is required. This review explores the underlying pathophysiology of GORD, its clinical presentation, risk factors, commonly applied diagnostic tools, and a detailed synthesis of original articles evaluating the prevalence of GORD, its influence on disease severity and current management strategies within the context of bronchiectasis. The prevalence of GORD in bronchiectasis ranges from 26% to 75%. Patients with co-existing bronchiectasis and GORD were found to have an increased mortality and increased bronchiectasis severity, manifest by increased symptoms, exacerbations, hospitalisations, radiological extent and chronic infection, with reduced pulmonary function and quality of life. The pathogenic role of Helicobacter pylori infection in bronchiectasis, perhaps via aspiration of gastric contents, also warrants further investigation. Our index of suspicion for GORD should remain high across the spectrum of disease severity in bronchiectasis. Identifying GORD in bronchiectasis patients may have important therapeutic and prognostic implications, although clinical trial evidence that treatment targeted at GORD can improve outcomes in bronchiectasis is currently lacking. Highlights: The prevalence of GORD in bronchiectasis ranges from 26–75%. Patients with both conditions have increased bronchiectasis severity and increased mortality. Identifying GORD in bronchiectasis may have important therapeutic and prognostic implications. Further research on the impact of GORD treatment on bronchiectasis outcomes in needed.